Assisted reproductive technologies in Thailand: 2001-2007 results generated from the ART Registry, Royal Thai College of Obstetricians and Gynaecologists - Teraporn Vutyavanich (2018)
Aim: To present the results of assisted reproductive technology (ART) performed in Thailand during 2001- 2007. Methods: All licensedART centers are obliged to submit annual reports on the number of patients, cycles,ART techniques and treatment outcomes to the Reproductive Medicine Subcommittee of the Royal Thai College of Obstetricians and Gynaecologists. Data from all centers were aggregated and analyzed retrospectively. Results: Cycles were categorized into fresh and frozen/thawed embryo transfer (FET) cycles. Initiated cycles in the first category for 2001 to 2007 were 2183, 2112, 2780, 2717, 3458, 3579 and 4288, respectively. FET cycles during the same period were 467, 558, 733, 768, 1136, 1210 and 1473, respectively. The average pregnancy rate for in vitro fertilization (IVF) was 28.9% per retrieval (range, 26-32.3%) or 33.8% per transfer (range, 30.7- 38.6%). Multiple pregnancies (of which 89.3% were twins) from all treatment procedures during this period were 11.4% (range, 9.2-14.5%). A congenital abnormality was reported in 0.56% of live births. The number of embryos per transfer in IVF decreased from 4.1 to 2.9, with no drop in pregnancy rates. Oocyte insemination by intracytoplasmic sperm injection (ICSI) was utilized more often than standard IVF, while gamete intrafallopian transfer and zygote intrafallopian transfer were almost completely replaced by IVF/ICSI. There was a significant difference in pregnancy rates (P < 0.01) when clinics were classified by cycle volumes (<100, 100-400 and >400 cycles/year). Conclusions: Despite many limitations, the data provided in this report will help patients, clinicians and policy makers understand the current situation of ART practice in Thailand. © 2011 Japan Society of Obstetrics and Gynecology.